CRANE OPERATORS` ANTHROPOMEASURES FACTORS IDENTIFICATION - Spasojević-Brkić, Vesna; Golubovic, Tamara; Milanović, Dragan D.; Brkić, Aleksandar (Journal of Applied Engineering Science, 2014)
Purpose of this paper is application of method based on multivariate statistical technique in order to determine critical dimensions of the crane cabin, which would maximize adjustability and ergonomics of the product, resulting in accommodation of wider range of the population and greater safety while operating. Multivariate statistical technique used for this purpose is factor analysis. Results of this research, conducted on a sample consisted of 83 crane cabin operators, showed that while designing a working space critical anthropomeasures take three-dimensional space, while their influence contributions in each dimension are determined with factor analysis. Results of this work are expected to be useful for industry in a way such that crane cabins’ designers can troubleshoot the dilemmas they encounter in their job. Using findings of this survey might lead to new designs of cabins that will offer less strenuous postures of operator, which consequently will improve productivity and safety.
Keywords: factor analysis; anthropomeasures; crane operators